Developing reinforcement of character education by implementing religious nationalism values - Syakroni, Agus; Setyosari, Punaji; Murtadho, Nurul; Sulthoni, Sulthoni (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Character education teaches ethical values in society and the state. It included religious nationalism values in the educational curriculum aimed at passing down the norms that apply to the life of a society. This study aimed to analyze the reinforcement of character education by implementing religious nationalism values in the school of Nasima, Method of this research used an ethnographic qualitative design. The research instruments utilized interview, observation, and documentation formats. Data collection was conducted by interviewing the foundation's chairman, school principal, teachers, and parents of students as core informants, and triangulation was carried out by interviewing educational supervisors and the education department of Semarang city. The results of the study revealed that reinforcement of character education by implementing religious nationalism values in the school of Nasima applied role play, exemplifying, the habituation of students to strengthening their good-manner behavioral culture, honesty, discipline, and the formation of religious nationalism character. The realization of education and religious character towards strengthening the values of nationalism can be implemented through four strategies, namely an integrated learning strategy between subjects carried out by teachers in the classroom, parental engagement strategy, school collaboration with society for strengthening the values of religious nationalism and their daily positive behavior through extracurricular activities and a partnership education strategy by involving agencies. government, private sector, religious leaders, and community leaders.